New tools for chemical modification of proteins - Cal, Pedro Miguel Saraiva Duarte, 1985- (2017)
Tese de doutoramento, Farmácia (Química Farmacêutica e Terapêutica), Universidade de Lisboa, Faculdade de Farmácia, 2014